Catheter-directed foam sclerotherapy for chronic venous leg ulcers. (December 2014) - Williamsson, Caroline; Danielsson, Peter; Smith, Lennart
Objectives: This study presents the results of catheter-directed foam sclerotherapy (CDS) for chronic venous ulcer refractory to compression treatment, four weeks and one year after treatment. Methods: In sum, 31 patients (32 limbs) with refractory chronic venous ulcer and duplex-verified superficial insufficiency were offered CDS. CDS was conducted with 10 ml of sclerosant foam of 3% polidocanol. Four weeks and one year after treatment, the patients were evaluated regarding ulcer healing and ultrasound appearance of the saphenous trunk. Results: CDS was successfully performed in all patients. After one year, 65% of the ulcers were healed. Only two (6%) recurred. 86% of the treated saphenous trunk were completely occluded, 3% was partly occluded and 10% were recanalised. No serious side effects occurred. Conclusions: CDS is one alternative of eliminating superficial venous reflux when treating refractory venous leg ulcers. This study suggests that the treatment is safe and induce a quick ulcer healing.